The stenopodainae (Hemiptera, Heteroptera) of Argentina - Diez, F. (2014)
In Argentina, 10 genera and 33 species of Stenopodainae (Hemiptera: Reduviidae) have been recorded. Diagnoses of the genera, subgenera and species are given, and an illustrated key to genera is provided. Six species are new records for Argentina and an additional seven species represent new records for provinces.